2022
DOI: 10.1136/bmj-2021-069008
|View full text |Cite
|
Sign up to set email alerts
|

Association of computed tomography screening with lung cancer stage shift and survival in the United States: quasi-experimental study

Abstract: Objective To determine the effect of the introduction of low dose computed tomography screening in 2013 on lung cancer stage shift, survival, and disparities in the stage of lung cancer diagnosed in the United States. Design Quasi-experimental study using Joinpoint modeling, multivariable ordinal logistic regression, and multivariable Cox proportional hazards modeling. Setting US National Cancer Database and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Lung cancer is the fastest-growing malignancy worldwide in morbidity and mortality, the most common cause of cancer death in men and the second leading cause of cancer death in women ( 1 ). Due to the popularization of low-dose computed tomography (CT) screening, the rate of detection of small pulmonary nodules (especially ground-glass nodules) has significantly increased in recent years, which makes early diagnosis and treatment of lung cancer more challenging ( 2 , 3 ). With the rapid development of minimally invasive techniques, traditional thoracotomy has been transformed into video-assisted thoracoscopic surgery (VATS) with less risk to patients ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the fastest-growing malignancy worldwide in morbidity and mortality, the most common cause of cancer death in men and the second leading cause of cancer death in women ( 1 ). Due to the popularization of low-dose computed tomography (CT) screening, the rate of detection of small pulmonary nodules (especially ground-glass nodules) has significantly increased in recent years, which makes early diagnosis and treatment of lung cancer more challenging ( 2 , 3 ). With the rapid development of minimally invasive techniques, traditional thoracotomy has been transformed into video-assisted thoracoscopic surgery (VATS) with less risk to patients ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A new study has found that low‐dose computed tomography lung cancer screening can lead to increases in the early detection of lung cancer and improvements in survival at the population level 1 . The results are encouraging because they demonstrate the potential for the widespread adoption of lung cancer screening to save lives.…”
mentioning
confidence: 99%
“…In this context, the linked study by Potter and colleagues (doi:10.1136/bmj-2021-069008) provides key evidence supporting the beneficial effect for lung cancer screening in people at high risk in the US despite the poor state of implementation 8. Using a quasi-experimental observational design, Potter and colleagues analyzed data from two large comprehensive US cancer registries—the National Cancer Database and the Surveillance Epidemiology End Results (SEER) program database.…”
mentioning
confidence: 99%